2013
DOI: 10.1016/s0020-1383(13)70209-2
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, knowledge, attitude and practice of speeding in two districts in Kenya: Thika and Naivasha

Abstract: , RTIs had the second highest increase in disability-adjusted life years between 1990 and 2010, compared to other conditions. This study aims to determine the prevalence, knowledge, attitudes and practices for speeding in Thika and Naivasha districts in Kenya. METHODS:Direct observations of vehicle speed were conducted at various times during the day and different days of the week on six roads selected based on a multi-stage sampling method in two districts to determine the prevalence of speeding. Roadside KAP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…In Kenya, the low prevalence of motorcycle helmet use remained unchanged, with around 30% of motorcycle riders correctly using helmets following the introduction of a traffic amendment bill in 2012, highlighting the need for a multi-faceted strategy that includes media campaigns and widespread enforcement in addition to legislative change for improving helmet use [66]. The authors reached a similar conclusion after studying the prevalence and attitudes towards drink driving in Cambodia, as Bachani et al [67] concluded that a multi-pronged and coordinated approach would be needed to effectively address this issue, including social marketing and public education campaigns, and enhanced enforcement measures.…”
Section: Enforcementmentioning
confidence: 82%
“…In Kenya, the low prevalence of motorcycle helmet use remained unchanged, with around 30% of motorcycle riders correctly using helmets following the introduction of a traffic amendment bill in 2012, highlighting the need for a multi-faceted strategy that includes media campaigns and widespread enforcement in addition to legislative change for improving helmet use [66]. The authors reached a similar conclusion after studying the prevalence and attitudes towards drink driving in Cambodia, as Bachani et al [67] concluded that a multi-pronged and coordinated approach would be needed to effectively address this issue, including social marketing and public education campaigns, and enhanced enforcement measures.…”
Section: Enforcementmentioning
confidence: 82%
“…Knowledge risk (Ishikawa and Naka, 2003;Massingham, 2010) is an analytical objective in many application domains such as IT (Varajao, et al, 2017), disaster risk management (UNISDR, 2014(UNISDR, , 2105aSpiekermann et al, 2015), fisheries (McDonald et al, 2017), supply chains (Raut et al, 2017), social risk, ecological (Asfaq, 2017;Lou et al, 2017), safety at sea (Goerlandt et al, 2017), safety critical systems (Scott-Parker and Oviedo-Trespalacios, 2017;Bachani et al, 2017) and indeed in the effectiveness assessment of Knowledge Management itself (Boy and Barna, 2005;Benoit, 2011;Ruzic-Dimitrijevic, 2014).…”
Section: Existing Approachesmentioning
confidence: 99%
“… 5 , 6 In addition, injuries from RTCs in Kenya had the second highest increase in DALYS between 1990 and 2010. 7 The lack of formalized resilient post‐injury psychosocial support systems in LMICs additionally aggravates the personal resource losses arising from RTCs beyond physical debilitation, financial incapacitation to mental distress. 8 Saidi and Mutisto 9 estimated the average duration of hospital stays (away from work) following RTCs in Kenya at 24.3 days at an average cost of Kenyan shillings 31,783 (US$282).…”
Section: Introductionmentioning
confidence: 99%
“… 15 The lack of preventive education campaigns, poorly monitored and uncoordinated road safety interventions, lack of coalition among road safety stakeholders, an increasing number of motorcycles, and poorly designed roads in congested urban areas ‐ are major contributing factors to RTCs in Kenyan settings. 9 , 12 , 13 For instance, whereas 57%−58% of cars in Kenya's main cities are driven above local speed limits, 7 seat belt use among drivers and passengers is reported at 12.5%. 1 Furthermore, helmet use is at 33% and 3% among motorcyclists and their passengers, respectively, 14 despite the known severe head injury risk for non‐helmet use.…”
Section: Introductionmentioning
confidence: 99%